1987
DOI: 10.1007/bf00281856
|View full text |Cite
|
Sign up to set email alerts
|

Artifacts in camera based single photon emission tomography due to time activity variation

Abstract: Image quality in single photon emission computed tomography (SPECT) using a rotating gamma camera is dependent on the time course of the tracer in the field of view. If acquisition times are slow compared to the tracer turnover, artifacts may occur in the reconstructed images. The properties of such artifacts were studied by computer simulation. Experimental projection data of point sources, cylindrical phantoms, and an anatomically realistic brain phantom were altered by sequentially weighting the projections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Distortions of the reconstructed slice due to timeactivity variation during acquisition can be visually assessed if the tracer concentration changes by more than a factor of 2 during one rotation (Bok et al 1987). As a possible solution Bok et al (1987) proposed performing multiple, fast SPET acquisitions and adding these studies together.…”
Section: Stationary Distribution Of the Radionuclidementioning
confidence: 99%
See 1 more Smart Citation
“…Distortions of the reconstructed slice due to timeactivity variation during acquisition can be visually assessed if the tracer concentration changes by more than a factor of 2 during one rotation (Bok et al 1987). As a possible solution Bok et al (1987) proposed performing multiple, fast SPET acquisitions and adding these studies together.…”
Section: Stationary Distribution Of the Radionuclidementioning
confidence: 99%
“…As a possible solution Bok et al (1987) proposed performing multiple, fast SPET acquisitions and adding these studies together. Then each projection image represents a mean distribution during the total acquisition time.…”
Section: Stationary Distribution Of the Radionuclidementioning
confidence: 99%
“…To date there exist some studies on FBP artifacts due to time-varying attenuation values [1], [2], [3] but there is no model to describe the characteristics of these artifacts. Therefore, in this paper we present a novel formalism to model reconstruction artifacts by a spatio-temporal filter in the object domain with terms that depend on the temporal derivatives of the attenuation values and derivative-weighted point spread functions.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the time-varying activity for the reconstruction of SPECT images was studied by Bok et al (1987) using simulations. They found that the time variation smeared the reconstructed images nonuniformly.…”
Section: Introductionmentioning
confidence: 99%
“…Both Bok et al (1987) and Nakajima et al (1992) assumed uniform uptake and washout of the tracer. Links et al (1991) assumed that there are cold defects in the myocardial tissue.…”
Section: Introductionmentioning
confidence: 99%